Perancangan Sistem Informasi Manajemen Klien Digital Agency PT. XYZ berbasis Website - Nuzulita, Nania; Sabana, Memoreza; Puri, Bingar Kenaya; Mentari, Retno; Christian, Kevin Nathanael (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
PT XYZ operates in the service sector and is a creative agency that produces product videos for its clients. During this time PT. XYZ has not implemented a management information system to manage the resources they have and maintain relationships with clients. Ease of access via various platforms is the reason why applications are built based on websites. The stages used in the research correspond to the stages in the software development life cycle (SDLC) in the planning, analysis and design phases. Interviews and literature studies are used to explore the business processes that occur. It was found that there were three types of users, namely super admin, admin, and client. The processes handled by the system include employee registers, client registers, recording incoming orders, project monitoring, and checking employee availability. The diagrams used to explain the system plan that will be created are use case diagrams, activity diagrams, sequence diagrams, and entity relationship diagrams. Lo-fi designs are also created using the Figma application. Further research can continue to the implementation, support and security stages.